Effectiveness and safety of the combination therapy of micro-needling and minoxidil in androgenetic alopecia of Indonesian men: a randomized controlled trial - Kara Adistri; Sondang P. Sirait; Rahadi Rihatmadja; Lili Legiawati; Wresti Indriatmi; Siti R.F. Saldi (PAGEPress Publications, 2024)
Introduction: Androgenetic alopecia (AGA) is the most common type of hair loss. Treatment options are limited. Microneedling, a minimally invasive technique can enhance hair growth by releasing growth factors. However, standardized protocol regarding the frequency, depth and duration has not been available. This study aims to determine the effectiveness and safety of the combination therapy of microneedling and minoxidil in AGA. Methods: This study was a randomized controlled clinical trial conducted over 12 weeks. Intervention group: a combination therapy of 4-weekly microneedling and 5% minoxidil, and control group got topical 5% minoxidil alone. Hair density and diameter were assessed using FotoFinder® trichoscale every 4 weeks. Results: A total of 36 male participants, between 26-51 years old, with Hamilton-Norwood type III-VI AGA were included. At the end of study, a significant increase in hair density was observed in the intervention group compared to control (95.6 vs 52.4 hair/cm², p<0.001), as was in hair diameter (18 vs 6 μm, p=0.004). Side effects, included itching and transient erythema, were well tolerated. Conclusion: The combination of 4-weekly microneedling and topical 5% minoxidil is effective in increasing both hair density and hair diameter, and safe to use in AGA patients.